Optimisation of complex distillation colomn systems using rigorous models - Hughes, Michael John (Department of Chemical Engineering, 2014)
Since distillation is still the most widely used separation technique used in the petrochemical industry, optimisation of these unit operations are important to minimise costs and maximise production. This thesis focuses on the development of a tool using rigorous non-equilibrium distillation models to optimise complex columns. Non-equilibrium distillation models are usually avoided in optimisation studies due to the time required to solve them, but this has been overcome by using a technique called orthogonal collocation in which the profiles in the columns are represented by polynomials of a lower order than would be required normally. This significantly reduces the process times and makes the use of non-equilibrium models a possibility in optimisation studies. The orthogonal collocation technique was applied to a packed distillation column model and shown to be effective in modelling the system. A system consisting of a distillation column with integrated external side reactors was chosen as a case study to investigate the use of the methods. These systems have been shown to be effective in certain circumstances in literature, when comparing them to other forms of process intensification, such as reactive distillation. The toluene disproportionation reaction was considered as a potential use for the technology and the optimisation tool was used to find optimum system configurations for achieving maximum toluene conversions and minimum costs. Nonlinear programming techniques were used initially to optimise these systems, but due to the discontinuities associated with multiple side streams, they were replaced by a genetic algorithm. Various system configurations were identified as achieving maximum conversions and minimum costs. These results were used in a comparison with results obtained from a literature study and the results showed significant promise. Unfortunately, the two studies did not have enough in common to truly produce a comprehensive result. This iv lead to further comparisons with another system using the same information. The results obtained in the toluene disproportionation case study showed that there was some possible benefits for using the side reactor systems, but the conventional system was still 30 and 60% cheaper in terms of capital and utility costs respectively. Another case study was investigated that looked at the synthesis of methyl acetate from acetic acid and methanol. The packed collocation model was used as a comparison with another investigation performed in literature (using equilibrium distillation models). Both showed comparable results, but still had significant differences. Costs were also compared between the side reactor system and a more conventional system for methyl acetate synthesis. The side reactor systems were found to be more cost effective than the conventional system. Additionally, an increase in the number of external reactors resulted in lower utility costs (mainly as a result of lower flow rates in the side streams). Overall, the reaction and process conditions are important considerations when deciding whether or not to use a side reactor system. For the gas phase toluene disproportionation reaction, the side reactor systems were not cost effective, when compared to the conventional system. However, the liquid phase methyl acetate reaction proved to be more conducive to side reactor systems in terms of cost. This thesis has shown the applicability of using rigorous disequilibrium distillation models in optimisation studies. The side reactor systems have been found to be complex systems that require a holistic approach to find optimum configurations instead of optimising individual process units.